The Effectiveness of Geographic Information System (GIS) Application in Land Use Planning at Mufulira Municipal Council, Copperbelt Province, Zambia - Peter, Zimba; Enock, Sakala; Beverly, Mushili (IJRDO-Journal of Applied Science, 2017)
This paperexamines the effectiveness of GIS application in land use planning at Mufulira Municipal Council after the adoption of GIS in 2008. Data was collected using semi-structured questionnaires, recorded interviews, Council GIS spatial data and written documents prepared on GIS.Comparative Analysis used to analyse collected data through the process of data documentation, conceptualization, categorization and examination. Results show that before the adoption of GIS, land use planning in Mufulirawas ineffective due to inadequate equipment.GIS implementation has therefore built capacity in the municipal council to prepare land use layout plans and control development in the municipality. TheCouncil’splanning department uses GIS on about 75 per cent of its physical planning functions. The paper concludes that despite GIS implementation having to some extent improved land use planning in Mufulira, poor maintenance has negatively affected the operations and expansion of the GIS unit. It is therefore recommended that the council invests in employing more GIS personnel, linking the GIS software to all departments of the council and acquiring a GIS server for effective land use planning.